Late Islamic fishing industry in the Gulf: the case of Kharāʾib al-Dasht, Jazīrat Faylakā (poster) - Pieńkowska, Agnieszka; Mierzejewska, Marta (Proceedings of the Seminar for Arabian Studies, 2018)
The following study presents the preliminary results of the research project conducted on Jazīrat Faylakā by the Kuwaiti-Polish Archaeological Mission (KPAM) with respect to the late Islamic fishing industry in the Gulf. Excavation works conducted at Kharāʾib al-Dasht revealed a fishing village dated to the late Islamic period. The interpretation of the function of the settlement was based not only on the abundance of finds and features related to fishing and fish processing — including net weights, anchors, and hooks — but also on the distribution of hearths, ovens, and finds of vessels for kitchen use. Furthermore, the underwater research of Jazīrat Faylakā’s coastal zone conducted by the KPAM revealed numerous underwater structures, including several concentrations of stone fish traps located near late Islamic settlements. Given the quantity and the quality of the infrastructure and equipment related to fish catching and fish processing that was attested on and around Jazīrat Faylakā, it seems very likely that the capacity of the fishing industry on the island greatly exceeded the needs of its inhabitants. In light of this observation, apart from fishing methods and fish-processing practices, the study also seeks to examine possible directions of the fish trade as well as its extent.